2014
DOI: 10.1002/adem.201400117
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Welding of Bulk Carbon Nanotube Conductors

Abstract: Incorporation of bulk carbon nanotube (CNT) conductors into energy and data systems can require new methods of making a functional interface with low electrical contact resistance and high mechanical strength. Ultrasonic welding has been shown as a viable technique for mechanically and electrically bonding commercial CNT materials (CVD) to copper foil. The mechanical strength across the ultrasonic welds was measured via dynamic mechanical analysis with single lap welds exceeding 350 kPa. The electrical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Nano-soldering techniques, are crucial and have been used to assemble nano-structures composed of nanowires, nanotubes, nanobelts or other functional nanomaterials. To date, several feasible nanosoldering techniques have been proposed, including laser heating, 15 soldering technique, 16,17 Joule heating, 18 high-energy electron beam irradiation, 19 ion beam deposition, 20 ultrasonic soldering 21 , thermal heating 22 and electron-beam-induced deposition. 23 Among these, the soldering technique with a sacrificial nanosolder has the greatest potential because of its controllability, flexibility and the crucial advantage of avoiding detrimental effects on the nano-objects to be joined.…”
Section: Here We Demonstrate That the Building Blocks Of Semiconductomentioning
confidence: 99%
“…Nano-soldering techniques, are crucial and have been used to assemble nano-structures composed of nanowires, nanotubes, nanobelts or other functional nanomaterials. To date, several feasible nanosoldering techniques have been proposed, including laser heating, 15 soldering technique, 16,17 Joule heating, 18 high-energy electron beam irradiation, 19 ion beam deposition, 20 ultrasonic soldering 21 , thermal heating 22 and electron-beam-induced deposition. 23 Among these, the soldering technique with a sacrificial nanosolder has the greatest potential because of its controllability, flexibility and the crucial advantage of avoiding detrimental effects on the nano-objects to be joined.…”
Section: Here We Demonstrate That the Building Blocks Of Semiconductomentioning
confidence: 99%
“…The electrical property degradation is less substantial for the samples that have been doped prior to thermal oxidation, indicating that the KAuBr 4 doping results in electrical conductivity retention after thermal oxidation to 400 °C. The thermally oxidized and then KAuBr 4 -doped CNT wires (400 °C in air, KAuBr 4 , ◆) exhibit a 16% reduction in resistance per length after doping, which indicates that the materials can be more effectively doped after removal of amorphous carbon 15 because the dopant can interact more favorably with the CNTs. Figure 8 summarizes the measured resting and working conductivities, normalized with respect to the initial conductivity (σ 0 ), as a function of increasing current density for the CNT wires exposed to various thermal oxidation and KAuBr 4 doping procedures.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The doping method involves introducing other elements to form unique structures, which makes the experimental process more complicated to control. The CNTs welding method involves breaking carbon–carbon bonds by high temperatures or chemical catalysis to regrow them. Welding methods can be classified into chemical vapor deposition, , ultrasonic, , high-energy particle beam irradiation, laser induced, , and Joule heat induced. , Among them, researchers have found that the Joule heat-welding method can realize CNTs welding at different scales and improve the electrical properties of CNTs by removing impurities, repairing defects, and enhancing crystallinity on carbon nanotubes. It can reach the melting temperature quickly, which is convenient and low cost.…”
Section: Introductionmentioning
confidence: 99%